Pengaruh Profitabilitas Dan Ukuran Perusahaan Terhadap Struktur Modal Pada Perusahaan Manufaktur Subsektor Farmasi Di Bursa Efek Indonesia Tahun 2017-2019 - Hendrawan Cipta Hartanto; Suwignyo Widagdo; Haifah Haifah (RELASI : JURNAL EKONOMI, 2023)
This study aims to determine the effect of profitability by using the calculation of return on assets and firm size by using the calculation of firm size on the capital structure by using the calculation of debt to equity ratio in manufacturing companies in the pharmaceutical sub-sector on the Indonesia Stock Exchange in 2017-2019. Meanwhile, the sample to be tested is in accordance with the research criteria that have been determined and the sampling technique is purposive sampling, and the companies that meet the sampling criteria are 8 companies. The data used in this study are secondary data from the annual financial statements of pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2017-2019 which were obtained from www.idx.co.id. The data management method uses multiple linear regression analysis with the help of SPPS 23 analysis tool. The results show that the profitability variable (return on assets) has a significant effect on the capital structure, while the firm size variable does not have a significant effect on the company's capital structure. pharmaceutical manufacturing sub-sector on the Indonesia Stock Exchange in 2017-2019.